PENGARUH LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA KANTOR PEMASARAN PERUMAHAN CITRA KEBUN MAS DI KARAWANG TIMUR - Intan Djuliyana; Suroso Suroso; Maman Mulya Karnama (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study aims to determine the effect of Work Environment and Work Discipline on Employee Performance of the Marketing Office of Citra Kebun Mas Karawang using quantitative verification. Research respondents were 65 employees in the marketing office. The method used was a questionnaire and SPSS 24 with a multiple linear regression approach. The research findings found that work environment has no positive and insignificant effect on employee performance, work discipline has a positive and significant effect on employee performance and work environment and work discipline have a positive and simultaneous effect on employee performance in the marketing office of Citra Kebun Mas housing.